Application Civic Virtue in Yogyakarta Natural School Through ‘Tata Krama Desa’ Subject - Fakhrul Kurniawan; Susan Fitriasari; Dede Iswandi (Jurnal Civicus, 2022)
This research is motivated by the weak internalization of the value of civility in education which is caused by not optimal learning in schools due to the learning environment factor.  Therefore the existence of the natural school as an innovation made to improve the purpose of optimal learning. One of the natural schools in Indonesia is Yogyakarta Nature School which has subjects of ‘tata krama desa’ as subjects that can internalize the civic virtue value. The purpose of this subject is to find out an overview about implementation of civic virtue value on the subject of ‘tata krama desa’ at the Yogyakarta Natural School.  This research uses a qualitative approach with a descriptive method. Data collection techniques carried out in this research were by means of observation, interviews, documentation studies, literature studies, and field notes. Data analysis techniques were carried out by reducing data, presenting data, drawing conclusions and verifying validating data by triangulation and member check. The results of the research show that in the subject of ‘tata krama desa’, the values of civic virtue have been implemented, this is based on the learning process, both in terms of planning, implementation, and assessment.